Front Matter JEMT Vol 2, No 1 (2021) - Editor, Editor (Lembaga Penelititan dan Pengabdian kepada Masyarakat - Institut Teknologi Adhi Tama Suraba, 2021)
Containing Cover, Editorial Board, List of Content, Back Cover including the ISSN barcode